Analysis of the Impact of authorship on the accessibility of scientific book publications by BRIN Publishing - Sarwendah Puspita Dewi; Sigit Sumarsono; Ike Iswary Lawanda (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. In publishing practices, authorship often becomes one of the aspects that influences the level of accessibility of a publication. This study aims to examine the differences in access between single authors and multiple authors, the differences in access between publications by BRIN-affiliated authors and non-BRIN-affiliated authors, as well as the differences in access between publications by authors with a single affiliation and those from different affiliations. Research Methods. This study used a quantitative method with descriptive analysis and hypothesis testing. The data were obtained from transaction logs on the BRIN Publisher’s OMP admin page, which recorded the number of accesses per publication from January to June 2025. Data Analysis. The data analysis technique was carried out by combining descriptive statistics and non-parametric statistics. Results. The results of this study indicate that certain classifications of authorship, such as the number of authors and the presence of BRIN-affiliated authors, do not significantly affect the number of accesses. In addition, no differences were found in access between BRIN-affiliated publications and those originating from outside BRIN. This study also found that collaboration influences the amount of access to a publication. Conclusion. The number of authors and BRIN affiliation do not directly affect the level of access, but cross-institutional collaboration has been proven to contribute positively to increasing user engagement.